(untitled) (Experimental biology, 2026)
The study aimed to develop and evaluate the effectiveness of a specialized immunostimulating product based on low-molecular-weight peptides isolated from mare’s and camel’s milk. The product was additionally enriched with biologically active compounds possessing antioxidant and immunomodulatory properties. The clinical study involved 20 volunteers aged 30-45 years divided into control and experimental groups. Participants consumed 90 g/day of the product for 20 days under conditions of daily physical activity. Humoral and cellular immunity parameters (IgG, IgA, IgM, T- and B-lymphocytes), lipid peroxidation markers (MDA, diene conjugates), and antioxidant defense indicators (catalase, superoxide dismutase, total antioxidant activity, vitamins A, E, and C) were assessed. The results demonstrated that physical exercise in the control group led to decreased immunoglobulin levels and signs of secondary immunodeficiency, along with increased oxidative stress markers. In contrast, administration of the specialized product resulted in a significant increase in IgG, IgA, and IgM levels, enhancement of T- and B-lymphocyte counts, reduction of lipid peroxidation products, and activation of antioxidant defense enzymes. The product stabilized humoral and cellular immunity and improved antioxidant status during physical stress. The findings confirm the pronounced immunostimulatory and antioxidant effects of low-molecular-weight peptides from mare’s and camel’s milk and support their use in the development of functional and preventive nutrition products.